STUDI PERKEMBANGAN GONAD IKAN BETOK (Anabas testudineus Bloch) DENGAN RANGSANGAN HORMON - Suriansyah Suriansyah; Agus Oman Sudrajat; Muhammad Zairin Jr (BERITA BIOLOGI, 2011)
The purpose of this study was to evaluate the effect of water in oil in water (w/o/w) emulsion containing 17a-methyltestosterone on gonad development of climbing perch. The results showed administration of 200 ug/kg 17o-methyltestosterone in w/o/w emulsion enhanced gonad development of climbing perch. In this treatment, testosterone concentration increased but estradiol-17p concentration decreased. Both hormones ranged 10,55-15,13 ng/dl and 0.96-5.66 ng/dl, respectively. This treatment also accelerated the development of egg diameter which were eggs e" 0.20 mm became 71.00% after 60 days, and development of egg nucleus position into germinal vesicle breakdown (GVBD) in day 60 was about 17.50%.